Lower Number and Percentage of Activated Natural Killer Cells in Colorectal Cancer Patients - Amie Vidyani; Iswan Abbas Nusi; Ulfa Kholili; Poernomo B Setiawan; Herry Purbayu; Titong Sugihartono; Ummi Maimunah; Budi Widodo; Husin Thamrin; Muhammad Miftahussurur (Acta Medica Indonesiana, 2023)
Background: Colorectal cancer is a type of cancer that begins in the colon and/or rectum tissue. Natural killer (NK) cells play a critical role in the first line of defense against infection and tumors, as well as in autoimmunity and hypersensitivity reactions. NK cells also play a role in regulating tumor cell growth and metastasis. The number and percentage of activated natural killer cells have been determined in patients with colorectal cancer and benign lesion. Methods: This was a cross-sectional observational analytic study. The number and percentage of activated NK cells in peripheral blood were determined using the flow cytometry method in 50 samples from patients who underwent colonoscopy and obtained a mass as evidenced by histopathological examination. Results: Among the 50 samples, 24 samples included in the colorectal cancer group and 26 samples from benign lesion group. The mean number of NK cells in colorectal cancer was 161.71 ± 62.666 cells/µL, benign lesion was 553.92 ± 269.173 cells/µL. The mean percentage of activated NK cells in colorectal cancer was 2.82 ± 1.19%, benign lesion was 5.10 ± 2.48%. There was a significant difference in the number of NK cells and the percentage of activated NK cells between colorectal cancer and benign lesion patients (p = 0.000). Conclusion: The number and activity of NK cells decreases in patients with colorectal cancer.